Rubella Serosurvey Among Future Healthcare Workers - Trevisan, Andrea; Mason, Paola; Nicolli, Annamaria; Maso, Stefano; Bertoncello, Chiara (Frontiers in Public Health, 2021)
Objective: Rubella is a very diffusive but relatively benign infectious disease unless contracted during pregnancy, when it causes congenital rubella syndrome. The aim of this research was to determine the prevalence and titer of anti-rubella antibodies in a population of future healthcare workers (students at the school of medicine). Methods: The cohort consisted of 11,022 students who underwent antibody analysis after presentation of a vaccine certificate. Results: Vaccination compliance was very high, particularly in younger students (born after 1995), reaching almost 100% (at least one dose). Unvaccinated students born before 1990 had high seropositivity (>95%), but this percentage dropped to zero among the youngest students. Variables affecting antibody titer included year of birth and sex. Considering only vaccinated students, a greater antibody response was observed if the vaccine was administered between 8 and 10 years of age. Female sex was associated with more significant (p < 0.0001) positivity and higher antibody titer after one and two doses. However, this difference appeared less consistent in relation to year of birth. Conclusions: The studied population exhibited excellent vaccination compliance, high seropositivity, and high antibody titer. Vaccine and immune coverage were higher than what is deemed necessary to achieve herd immunity.